Oil Formation Volume Factor Empirical Correlations for some Libyan Crude Oils (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Physical properties of reservoir fluid arenecessary for different field applications. Among those properties is the Oil Formation Volume Factor (Bo). It isone of important property for both reservoir andproduction engineering. In many situations, laboratorymeasurement is not possible either because ofunavailability of liquid oil samples or budget constraints,Hence, proper empirical correlations to predict formationvolume factor come to rescue. The purpose of thisexploration is to test the performance of the most commonpublished Oil Formation Volume Factor correlations forselected Libyan crude oils. Statistical analysis is thecriteria adopted for the evaluation in this study. Cross plottechnique is also applied to check the performance of thecorrelation and it gave the same index of the statisticalcriteria method. Accuracy of these correlations has been confirmed bycomparing the obtained results of these correlations withexperimental data gathered from our labs for Libyan oilreservoirs. It was observed that, there is acceptableagreement between predicted results with experimentalresults.